In silico evidence of beauvericin antiviral activity against SARS-CoV-2. (February 2022) - Al Khoury, Charbel; Bashir, Zainab; Tokajian, Sima; Nemer, Nabil; Merhi, Georgi; Nemer, Georges
Abstract: Background: Scientists are still battling severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for the coronavirus 2019 (COVID-19) pandemic so human lives can be saved worldwide. Secondary fungal metabolites are of intense interest due to their broad range of pharmaceutical properties. Beauvericin (BEA) is a secondary metabolite produced by the fungus Beauveria bassiana . Although promising anti-viral activity has previously been reported for BEA, studies investigating its therapeutic potential are limited. Methods: The objective of this study was to assess the potential usage of BEA as an anti-viral molecule via protein–protein docking approaches using MolSoft. Results: In-silico results revealed relatively favorable binding energies for BEA to different viral proteins implicated in the vital life stages of this virus. Of particular interest is the capability of BEA to dock to both the main coronavirus protease (Pockets A and B) and spike proteins. These results were validated by molecular dynamic simulation (Gromacs). Several parameters, such as root-mean-square deviation/fluctuation, the radius of gyration, H-bonding, and free binding energy were analyzed. Computational analyses revealed that interaction of BEA with the main protease pockets in addition to the spike glycoprotein remained stable. Conclusion: Altogether, our results suggest that BEA might be considered as a potential competitive and allosteric agonist inhibitor with therapeutic options for treating COVID-19 pending in vitro and in vivo validation. Graphical abstract: Image 1 Highlights: BEA binds with strong affinity to allosteric and orthosteric drug target sites of the SARS-CoV-2 main protease. BEA is a potential competitive and allosteric agonist inhibitor with therapeutic options for treating COVID-19.